Preparation and Characterization of Chitosan Binder-Based Electrode for Dye-Sensitized Solar Cells - En Mei Jin; Kyung-Hee Park; Ju-Young Park; Jae-Wook Lee; Soon-Ho Yim; Xing Guan Zhao; Hal-Bon Gu; Sung-Young Cho; John Gerard Fisher; Tae-Young Kim (International Journal of Photoenergy)
A chitosan binder-based TiO2 photoelectrode is used in dye-sensitized solar cells (DSSCs). Field-emission scanning electron microscope (FE-SEM) images revealed that the grain size, thickness, and distribution of TiO2 films are affected by the chitosan content. With addition of 2.0 wt% chitosan to the TiO2 film (D2), the surface pore size became the smallest, and the pores were fairly evenly distributed. The electron transit time, electron recombination lifetime, diffusion coefficient, and diffusion length were analyzed by IMVS and IMPS. The best DSSC, with 2.0 wt% chitosan addition to the TiO2 film, had a shorter electron transit time, longer electron recombination lifetime, and larger diffusion coefficient and diffusion length than the other samples. The results of 2.0 wt% chitosan-added TiO2 DSSCs are an electron transit time of  s, electron recombination lifetime of  s, diffusion coefficient of  cm2 s−1, diffusion length of 14.81 μm, and a solar conversion efficiency of 4.18%.